The International Humanitarian Law Protection On Civilians From Sexual Exploitation And Abuse Committed By The United Nations Peacekeepers - Revalyani Revalyani; Sophia Listriani (Fakultas Hukum Universitas Syiah Kuala, 2018)
United Nations has operated its peacekeeping operation for decades since 1990s and well known for engagement in sexual exploitation and abuse, particularly, by troops of contributing countries. The engagement to violence is contrast to protecting civilian mandate of operation. In international Humanitarian Law, sexual exploitation and abuse is classified into rape and other form of sexual violence which are prohibited in legal documents such as Geneva Conventions 1949 and Additional Protocols 1977. The focus of the research is to describe the protection of civilian covered under International Humanitarian Law, to comprehend the Sexual Abuse and Exploitation in International Humanitarian Law and to identify how International Humanitarian Law account the sexual abuse and exploitation in United Nations peacekeeping operation. This research is conducted under normative method. The data is accumulated predominantly on secondary data beside primary and tertiary data by library research through identifying and locating sources that provide actual information or opinion of expert. Civilian protection is enacted in Common Article 3 of Geneva Conventions 1949. Additional Protocol I and II 1997 to Geneva Conventions 1949 stipulate the protection in Article 51 (3) of first Protocol and Article 13(3) of second Protocol. Rape and other kinds of sexual violence are prohibited in Geneva Conventions 1949 and Protocols 1977 to the Conventions. Specifically in Common Article 3 of the Conventions 1949 which implicitly prohibits sexual violence and explicitly prohibits in Article 27 of the fourth Geneva Convention 1949. On the other hand, Additional Protocol I of 1977 in Article 75 (2) (b) provides the protection upon personal dignity and Article 76 (1) and Article 77 (1) of the Protocol provides the protection specifically women against the sexual violence. Second Protocol also sets the prohibition in Article 4 (2) (e). United Nations enforce international humanitarian law through its legal document of Secretary-General’s bulletin ST/SGB/1999/13 “Observance by United Nations forces of international humanitarian law”. The violation of the rules may lead the violators to disciplinary action. But still, the jurisdiction of investigation and prosecution is behalf of national state of the perpetrator him/herself. The exclusive jurisdiction is reflected in any legal documents. However, in the matter of IHL, the law can be imposed in states military court through the military manuals. Therefore, the recommendation to the issue matters is arisen several numbers include United Nations shall name and shame the states who fail to investigate and prosecute their accused troops, United Nations shall actively work with the states to fill the gap of accountability procedure, and States or United Nations shall establish a court where the allegation can be prosecuted in consent of parties of state as contributors.